Hoffmann Reflex Measured From Lateral Gastrocnemius Is More Reliable Than From Soleus Among Elderly With Peripheral Neuropathy - Song, Qipeng; Sun, Mengzi; Lewis, Kelsey; Choi, Jung Hun; Manor, Brad; Li, Li (Frontiers in Aging Neuroscience, 2022)
Introduction Peripheral neuropathy (PN) affects up to 20% of the population over the age of 60. Hoffmann reflex (H-reflex) may assess PN adaptation by measuring the function of the peripheral neural system and central nervous system (CNS) modulation. This project aimed to find a reliable muscle among triceps surae muscles during standing and walking among the PN population. Materials and Methods Sixteen older adults (> 65 years of age) diagnosed with PN were recruited in this study. The H-reflex test was conducted on the muscle belly of the soleus (SOL), the medial (MG), and lateral gastrocnemius (LG) during standing and walking (heel contact, midstance, and toe-off phases). All measurements were collected on two occasions, separated by at least 7 days. Intraclass correlation coefficients (ICCs) and their confidence intervals (CIs) were used to examine the consistency of the H-reflex outcome variables in the repeated tests for all three tested muscles. Results The ICCs of H-index during standing and the three walking phases were poor to moderate in SOL (0.486∼0.737) and MG (0.221∼0.768), and moderate to high in LG (0.713∼0.871). The ICCs of H/M ratio were poor to moderate in SOL (0.263∼0.702) and MG (0.220∼0.733), and high in LG (0.856∼0.958). Conclusion The H-reflex of LG was more reliable than SOL and MG during standing and walking among older adults with peripheral neuropathy. It is crucial for future studies in this population to study H-reflex of LG, not SOL and MG, for more reliable results.